Professional journey of expert teacher educators - Hashim, Hashimah; Ahmad, Shamsudin; Ismail, Ismi Arif (2011)
The novice can learn from the experts, but knowledge and expertise acquired by the experts are tacit in nature and difficult to share. To access this knowledge, the experts need to make their expertise explicit. Research on teacher educators is so sparse and the literature is relatively old. Teacher educators as researchers tend to study teachers more than teacher educators. This group of professionals is important because the expertise of the teacher educators is one of the contributions towards excellence in teacher education. This study is regarding the professional journey of expert teacher educators which contributes towards the teacher educators’ professional development. The objectives are to explore the main concern of the expert teacher educators in their journey to become experts and to produce theories based on data in the substantive area. The tentative rudimentary framework of this study opts to view how reflection-on-action deepens in the course of a career which also suggests that the capacity to reflect on action so as to engage in a process of continuous learning was one of the defining characteristics of professional practice. The informers’ concerns based on reflection-on-action are data to the building blocks of a tentative theory of the experts’ professional journey in this study.